DO ISLAMIC BANKS IN INDONESIA TAKE EXCESSIVE RISK IN THEIR FINANCING ACTIVITIES? - Muhamad Anindya Hiroshi Purbayanto; Taufik Faturohman; Yulianti Yulianti; Arson Aliludin (Journal of Islamic Monetary Economics and Finance, 2022)
This study analyzes the risk-taking behavior of Indonesian Islamic Banks by examining whether the relation between financing Growth rate and non-performing financing (NPF). We employ threshold regression models and bank-level data of 24 Islamic banks (full-fledged Islamic banks and Islamic banking windows) covering the period from 2009 to 2019. We find evidence for the excessive risk-taking of Islamic Banks. More specifically, while the relation between NPF and FGR is negative when the one-lagged NPF is below the threshold (estimated to be 5.42%), it turns positive once it is above the threshold. This means that banks with NPF above the 5.42 percent threshold tend to take risky loans.